Toning Down Abraham: Arthur Golding’s 1577 Translation, A Tragedie of Abraham’s Sacrifice - Graham, Anne G. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
Arthur Golding was a prolific Elizabethan translator, most famous for his rendering of Ovid’s Metamorphoses. In 1577, he translated Théodore de Bèze’s 1550 tragedy, Abraham sacrifiant. While the Huguenot’s play has been widely studied, Golding’s translation has received almost no scholarly attention. This article aims to correct this oversight through a comparison of Golding’s version with the original. The analysis shows that Golding in large part employs a deferential approach to the translation of Bèze’s play, one that is in keeping with the religious nature of the text. However, this article also demonstrates that Golding switches translation styles in key moments of the Huguenot tragedy, in particular where Bèze emphasizes the scandalous nature of God’s command and Abraham’s dilemma. In these moments, Golding uses a variety of strategies to lessen the scandalous nature of the text, thereby “pre-digesting” the material for the reader. This editorial tactic will be viewed in relation both to the interpretive approach espoused by Golding in his preface to the Metamorphoses, and to John Calvin’s treatise on offense (scandal), which Golding was translating at the same time as Ovid’s poem.